Book Study Teams: Empowering Others to Become Leaders in the 21st Century - Gerald D. Bailey; Randal E. Bagby; Rick Doll (Educational Considerations, 2003)
Over the last five years, the department of Educational Administration and Leadership at Kansas State University has been engaging in a series of university-school district partnerships to improve the training of school leaders.